Ensino de física e autismo: articulações no ensino médio - Borges, Aline dos Anjos Davi (2021)
In this work, we sought to understand the teaching of Physics and its articulations in high school, with a view to learning individuals with autism. This research comprises a qualitative approach, organized in two stages: In the first stage, we conducted a bilbliographic and documentary research, with the objective of knowing the theme, and understanding the specificities of the autistic spectrum, and teaching Physics. In the second stage we seek to analyze the Physics textbook, more specifically the content of Mechanics, and to what extent it assists the teacher as a pedagogical resource to be used in the classroom. For the analysis of the data, the characterization of autism was used as a theoretical reference, and its implications in relation to the specificities of learning for these individuals, strategies inspired by Content Analysis (CA) were adopted, contemplating the following categories of context: Application of knowledge (AC), Scientific Description of facts and processes (DC), Understanding of social reality (CRS), and Transformation of social reality (TRS), also adopted subcategories, with the objective of expanding perceptions in the context analyzed. These subcategories were Near Everyday (CP) and Far Away (CD). From the preliminary analysis it was possible to verify that little was discussed about learning for individuals with autism, especially in the teaching of Physics, which leads us to believe in the relevance of analyzing teaching strategies that address this need, with a view to including these individuals and their effective learning. It is believed that these results may contribute to the teaching practice of the physics teacher and assist in the delimitation of new themes, contributing to the development of studies that fill gaps in the literature.